2009
DOI: 10.1093/hmg/ddp119
|View full text |Cite
|
Sign up to set email alerts
|

The STAT4 gene influences the genetic predisposition to systemic sclerosis phenotype

Abstract: The aim of this study was to investigate the possible role of STAT4 gene in the genetic predisposition to systemic sclerosis (SSc) susceptibility or clinical phenotype. A total of 1317 SSc patients [896 with limited cutaneous SSc (lcSSc) and 421 with diffuse cutaneous SSc (dcSSc)] and 3113 healthy controls, from an initial case-control set of Spanish Caucasian ancestry and five independent cohorts of European ancestry (The Netherlands, Germany, Sweden, Italy and USA), were included in the study. The rs7574865 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(122 citation statements)
references
References 26 publications
6
110
1
5
Order By: Relevance
“…The MAF for each SNP was consistent with the values reported in studies of systemic sclerosis. [11][12][13][14][15][16][17][18][19] Two SNPs (rs11642873 and rs1234314) did not pass quality control because of low call rates on one of the genotyping platforms (see supplemental Table 1, available on the Blood Web site). Supplemental Table 2 shows the genotype distributions and MAFs for each SNP, according to the presence or absence of sclerosis.…”
Section: Candidate Genes and Snpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MAF for each SNP was consistent with the values reported in studies of systemic sclerosis. [11][12][13][14][15][16][17][18][19] Two SNPs (rs11642873 and rs1234314) did not pass quality control because of low call rates on one of the genotyping platforms (see supplemental Table 1, available on the Blood Web site). Supplemental Table 2 shows the genotype distributions and MAFs for each SNP, according to the presence or absence of sclerosis.…”
Section: Candidate Genes and Snpsmentioning
confidence: 99%
“…MAFs were similar between donors and recipients, and are consistent with results from studies of patients with systemic sclerosis. [11][12][13][14][15][16][17][18][19] ‡All ORs were derived from allelic genetic models.…”
Section: Candidate Genes and Snpsmentioning
confidence: 99%
“…As in the case of SLE, polymorphisms in the genes encoding proteins involved in the activation or activity of type I IFNs are also associated with a predisposition to develop certain of these diseases. For example, polymorphisms in the STAT4 and IRF5 genes are associated with an increased risk of developing systemic sclerosis, an autoimmune connective tissue disorder characterized by fibrosis of multiple organs and a type I IFN signature [Dieude et al 2009;Ito et al 2009;Rueda et al 2009]. …”
Section: Therapeutic Advances In Drug Safety 2 (3)mentioning
confidence: 99%
“…Given the key role played by type I IFNs in the innate immune response it is perhaps not surprising that dysregulation of the type I IFN pathway can under certain circumstances lead to induction or exacerbation of autoimmune disease in predisposed individuals [Burdick et al 2009]. Thus, polymorphisms in the genes encoding key intermediates in the type I IFN pathway have been identified as risk factors for the development of autoimmune disease [Dieude et al 2009;Ito et al 2009;Rueda et al 2009], and a number of IFN-induced proteins are up regulated in active disease [Ronnblom et al 2006;Baechler et al 2003]. Furthermore, a recent report has shown that a loss of function variant in the gene encoding MAVS, a key antiviral molecule downstream of the cytosolic doublestranded RNA sensors RIG-I and MDA-5, is associated with low type I IFN production and the absence of anti-RNA-binding protein autoantibodies in a novel subphenotype of SLE [Pothlichet et al 2011].…”
Section: Adverse Events: Underlying Mechanisms and Clinical Implicationsmentioning
confidence: 99%
“…This SNP results in the production of a different isotype from IRF5 leading to a different transcription of target pro-inflammatory cytokines which are known to increase the risk for developing SLE [131]. Next to that, recent data show an association between STAT-4 SNPs and disease phenotype favoring limited SSc [132]. Both associations suggest a role for TLR signaling and the IFN pathway in SSc as shown for SLE and RA but further research to unravel consequences of these SNPs is needed.…”
Section: Systemic Sclerosismentioning
confidence: 99%